A novel single‐cell method provides direct evidence of persistent DNA damage in senescent cells and aged mammalian tissues. Issue 2 (26th January 2017) - Galbiati, Alessandro; Beauséjour, Christian; d'Adda di Fagagna, Fabrizio
Summary: The DNA damage response (DDR) arrests cell cycle progression until DNA lesions, like DNA double‐strand breaks (DSBs), are repaired. The presence of DSBs in cells is usually detected by indirect techniques that rely on the accumulation of proteins at DSBs, as part of the DDR. Such detection may be biased, as some factors and their modifications may not reflect physical DNA damage. The dependency on DDR markers of DSB detection tools has left questions unanswered. In particular, it is known that senescent cells display persistent DDR foci, that we and others have proposed to be persistent DSBs, resistant to endogenous DNA repair activities. Others have proposed that these peculiar DDR foci might not be sites of damaged DNA per se but instead stable chromatin modifications, termed DNA‐SCARS. Here, we developed a method, named 'DNA damage in situ ligation followed by proximity ligation assay' (DI‐PLA) for the detection and imaging of DSBs in cells. DI‐PLA is based on the capture of free DNA ends in fixed cells in situ, by ligation to biotinylated double‐stranded DNA oligonucleotides, which are next recognized by antibiotin anti‐bodies. Detection is enhanced by PLA with a partner DDR marker at the DSB. We validated DI‐PLA by demonstrating its ability to detect DSBs induced by various genotoxic insults in cultured cells and tissues. Most importantly, by DI‐PLA, we demonstrated that both senescent cells in culture and tissues from aged mammals retain true unrepaired DSBs associated with DDR markers.